Non‐destructive evaluation of in‐place rehabilitated concrete pavements - Gopalakrishnan, Kasthurirangan; Kim, Sunghwan; Ceylan, Halil (Journal of Civil Engineering and Management, 2010)
Several in‐place rehabilitation techniques have been used before placing an Asphalt Concrete (AC) overlay on Portland Cement Concrete (PCC) pavements in attempts to minimize reflection cracking. Among these techniques, “rubblization” of PCC has been recognized to be the most utilized procedure for the mitigation of reflection cracking in US. This paper presents the practices on the use of rubblization in US and discusses the performance of this technique based on field evaluation. The specifications for the rubblization procedure used by state Department of Transportation (DOT) in US were reviewed. To evaluate the performance of rubblization technique, the structural and the surface conditions of AC overlaid pavements with rubblized PCC layer are compared to those with virgin PCC layer. A series of field experiment tests were carried out on six representative AC overlaid pavements with both rubblized PCC and virgin PCC in Iowa during 2007. The field experiment tests include the Nondestructive (NDT) and destructive tests, and the distress survey. Deflection Basin Parameters (DBPs) were derived from NDT test results to characterize the structural condition of pavements. The results indicate that the rubblized PCC layer has strength comparable to that of virgin PCC layer and has better performance under that structural condition. First Published Online: 10 Feb 2011